2012
DOI: 10.1007/978-1-4419-9796-8_43
|View full text |Cite
|
Sign up to set email alerts
|

Long term condition monitoring of tapestries using image correlation

Abstract: Digital Image Correlation (DIC) is used to extract non-contact full-field three-dimensional displacement and inplane strains from an historic tapestries. A DIC-based approach is devised that allows the effect of RH variations on a tapestry to be quantified. A historical tapestry has been monitored in a closely controlled environment and in the natural environment. The results revealed that very small variations in RH can have significant effects on strain. An automated long term monitoring approach has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…14, 15 Recently it has been successfully applied in the field of conservation of art for strain monitoring in historic tapestries. 16,17 The authors demonstrated the feasibility of the DIC method for non-contact fullfield quantitative analysis of three-dimensional displacement and in-plain strains in large textiles. Moreover, the method has been used for a long-term monitoring of textile deformations caused by fluctuations of climatic conditions in museum environment.…”
Section: Methodsmentioning
confidence: 99%
“…14, 15 Recently it has been successfully applied in the field of conservation of art for strain monitoring in historic tapestries. 16,17 The authors demonstrated the feasibility of the DIC method for non-contact fullfield quantitative analysis of three-dimensional displacement and in-plain strains in large textiles. Moreover, the method has been used for a long-term monitoring of textile deformations caused by fluctuations of climatic conditions in museum environment.…”
Section: Methodsmentioning
confidence: 99%
“…Since high-resolution CCD and CMOS detectors became available, DIC appeared to be the method to satisfy these requirements. It has been used successfully for examination of strains in tapestries [31][32][33]. The DIC method [34] enables noncontact, full-field measurements of displacements, simultaneously in two (2D DIC) [35][36][37] or three dimensions (3D DIC) [38][39][40], with an accuracy scalable with the field of measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Since its inception in the early 1980s, the basic algorithm went through a series of significant modifications [2,3] that substantially broadened the area of application and improved the robustness. This advantage over standard pointwise techniques, including strain gauges, geodesy equipment, or optical fiber sensors, attracted the attention of researchers and experts from a variety of different domains such as building engineering [4], power engineering [5], and art conservation [6,7]. This advantage over standard pointwise techniques, including strain gauges, geodesy equipment, or optical fiber sensors, attracted the attention of researchers and experts from a variety of different domains such as building engineering [4], power engineering [5], and art conservation [6,7].…”
Section: Introductionmentioning
confidence: 99%